The effect of anti-tissue antibodies in healthy volunteers - Seguin, P. (British Homeopathic Journal, 1988)
There is currently no aetiological therapy for Acquired Immune Deficiency Syndrome (AIDS). Treatment is directed only towards the opportunistic diseases which develop in these patients. The author shows that the use of antilymphocyte serum (ALS), normally used following organ transplantation, is capable of inducing biological and clinical manifestations which are analogous to those of patients suffering from AIDS.Recent work in immunology demonstrates that very small doses of specific anti-tissue antibodies are capable of inducing specific biological modifications of the immune response in healthy subjects.In view of the similia principle, the author opens a new field of research and proposes a specific treatment of infection with HIV in the light of his clinical experiment. This treatment may be of value in healthy carriers as well as patients who have already developed some clinical manifestations.